Diabetic retinopathy: quantitative variation in capillary basement membrane thickening in arterial or venous environments. Issue 2 (February 1994) - Stitt, A W; Anderson, H R; Gardiner, T A; Archer, D B
Abstract : Diabetes mellitus was induced in male beagles by a single injection of an alloxan and streptozotocin cocktail and fasting blood sugar levels maintained between 15 and 20 mmol/l. Five years after induction of diabetes, three diabetic animals were sacrificed, together with sex and age-matched controls, and the retinas fixed for either transmission electron microscopy (TEM) or trypsin digestion. In TEM specimens, capillaries in close proximity to the major vessels were designated as either AE (arterial environment) or VE (venous environment) and the thickness of their basement membranes (BMs) measured using an image analyser based two dimensional morphometric analysis system. Results show that the BMs of retinal capillaries from the diabetic dogs were significantly thicker than those from control dogs. Furthermore, within the diabetic group the AE capillaries had thicker BMs than VE capillaries (p < or = 0.05). The controls, however, showed no significant difference in BM thickness between AE and VE capillaries. Although many of the capillaries designated as AE or VE would actually have been derived from the opposite side of the circulation, with respect to BM thickness, they conformed to values of their specific group. The conclusion is that diabetic capillaries are more vulnerable to BM thickening in an arterial environment than in a venous environment.